2020
DOI: 10.3390/app10155200
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Groundwater Hydraulics to Design a Groundwater Level Monitoring Network for Sustainable Management of Fresh Groundwater Lens in Lower Indus Basin, Pakistan

Abstract: The over-extraction of groundwater from thin fresh groundwater lenses is a threat to the livelihood of farmers in the Lower Indus Basin (LIB). It is essential to monitor and regulate this pumping to sustain fresh groundwater lenses. In this study, we applied a modelling approach in combination with geostatistical analysis to identify the critical locations to monitor the groundwater levels for sustaining fresh groundwater in the LIB. Our approach included four steps: (i) simulating temporal heads using a calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several studies in the Central Indus Basin used groundwater modelling to assess the impact of external stresses (e.g., [14,15]). In the Lower Indus Basin, groundwater modelling studies have been conducted at small spatial scales to study groundwater hydraulics and hydro salinity behaviour (e.g., [16][17][18]). Studies related to the impacts of climatic change on groundwater in the Lower Indus Basin are limited, especially at the regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the Central Indus Basin used groundwater modelling to assess the impact of external stresses (e.g., [14,15]). In the Lower Indus Basin, groundwater modelling studies have been conducted at small spatial scales to study groundwater hydraulics and hydro salinity behaviour (e.g., [16][17][18]). Studies related to the impacts of climatic change on groundwater in the Lower Indus Basin are limited, especially at the regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [ 19 ] demonstrated a modelling strategy combined with geostatistical analysis to highlight the key areas for groundwater level monitoring to maintain fresh groundwater in the Lower Indus Basin, Sindh, Pakistan. Khan et al [ 20 ] evaluated the optimization of groundwater conditioning factors, the evaluation of groundwater potential, and other parameters for groundwater resource management in Northern Pakistan.…”
Section: Introductionmentioning
confidence: 99%